Dissociative psychosis or dissociative schizophrenia? Comparison of two phenomena - Mahir Akbudak; Hasan Belli; Hasan Gökçay; Uğur Takım (BMC Psychiatry)
Abstract Background In recent years, researchers have reported crucial advances in the understanding of “Dissociative psychosis” and “Dissociative schizophrenia”. While clinical studies in this area have been sustained for well, it remains to be established for some aspects that a clear and valid relationship exists between dissociation, childhood traumatic experiences, and schizophrenia or psychotic spectrum disorders. Methods: To test such hypotheses, we divided the patients into two groups; the first group consisted of patients with psychotic disorders not otherwise specified (PNOS), and the second group consisted of schizophrenic patients. Further, we have investigated the symptoms of dissociation, its relation to childhood traumatic experiences, and psychotic symptoms. The study included 81 patients diagnosed with schizophrenia according to DSM-5 diagnostic criteria and 81 patients diagnosed with PNOS. Researchers assessed participants using the Dissociation Questionnaire (DIS-Q), the Childhood Trauma Questionnaire (CTQ, and the Positive and Negative Syndrome Scale (PANSS). Results: The present study showed that patients with PNOS have higher dissociation and childhood traumatic experiences scores than the schizophrenic group and that the patients with the PNOS group yielded elevated physical abuse, emotional abuse, emotional neglect, sexual abuse, and bodily neglect scores as compared to the schizophrenic group. However, the PNOS group exhibited significantly lower PANSS total, PANSS negative, and PANSS general psychopathology scores compared to the schizophrenia group. DIS-Q and total CTQ level were also significant predictors of PNOS. Conclusion: Our results of statistical comparisons have supported the existence of the clinical manifestation known as dissociative psychosis, not dissociative schizophrenia.